Highly complex ceramic cores for investment casting applications made possible by additive manufacturing - Alice Rosa; Oscar Santoliquido; Francesco Camerota; Rose Ghaderi; Federico Barcelli; Alberto Ortona (Open Ceramics)
In this work, high quality complex ceramic cores for the investment casting are successfully produced employing the ceramic digital light processing additive manufacturing technology. Starting from the CAD model of a representative turbine blade core, an in-depth study of the complex features is performed to optimally place the printing supports and ensure printability and dimensional and geometrical accuracy of the sintered core. Green silica cores are produced layer-by-layer by selectively photo polymerize a specifically designed photosensitive SiO2-based slurry. The ceramic bodies are obtained through thermal de-binding and sintering at 1220 °C for 6 h. A material qualification is performed highlighting desired properties at microstructural and mechanical levels when compared to a silica-based material produced by traditional methods.